DEVELOPING A MODEL FOR STRUCTURING EDUCATIONAL PERSONNEL ROLES IN MADRASAH ALIYAH TO IMPROVE EDUCATIONAL SERVICE QUALITY - Mawardi Mawardi; Aspuriah Aspuriah; Siti Khodijah (Benchmarking: Jurnal Manajemen Pendidikan Islam, 2024)
The quality of educational services is a key indicator of effective management in Islamic educational institutions, including Madrasah Aliyah. While previous studies have largely emphasized the roles of principals and teachers, limited attention has been given to educational personnel as strategic actors within the educational service quality system. This study aims to develop a managerial model for structuring the roles of educational personnel in Madrasah Aliyah oriented toward improving educational service quality. Employing a qualitative research approach, data were collected through in-depth interviews, non-participant observation, and documentation studies involving madrasah principals, heads of administration, educational personnel, and teachers. The data were analyzed using thematic qualitative analysis. The findings reveal that educational personnel role arrangements remain predominantly administrative and are characterized by role ambiguity, overlapping responsibilities, weak coordination mechanisms, and the absence of standardized service procedures and service-based performance evaluation. These conditions result in inconsistent and reactive educational service delivery. Based on empirical findings, this study proposes a managerial model that integrates clear role structuring, updated job descriptions, standardized service procedures, institutionalized coordination mechanisms, service-indicator-based performance evaluation, and continuous leadership supervision. This study contributes to the field of Islamic Education Management by repositioning educational personnel as strategic actors in educational service quality assurance and by strengthening the linkage between managerial systems, service quality improvement, and value-based professionalism in madrasah governance.